2010
DOI: 10.1002/bjs.6991
|View full text |Cite
|
Sign up to set email alerts
|

Risk of reintervention after endovascular aortic aneurysm repair

Abstract: Background:The role of symptomatic presentation in directing reintervention after endovascular aortic aneurysm repair (EVAR) was investigated.Methods: All patients undergoing infrarenal EVAR between 2001 and 2009 were studied. Those needing reintervention were divided into symptomatic and asymptomatic presentations. Kaplan-Meier survival curves were used to calculate freedom from reintervention, and log rank tests for subgroup analyses. Multivariable analysis identified risk factors for reintervention. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 26 publications
3
91
1
Order By: Relevance
“…17 In another study of 1768 patients, 18 our patient cohorts were small, our total reintervention rate (7.4%) in the CxL group was lower than that reported in large single center series (12.5% to 19.2%). 18,21 Besides stent-graft design, aortoiliac axis geometry, and the distal landing zone, limb orientation could contribute equally to limb thrombosis. The geometry of the conduit is, in fact, one of the most important determinants of local flow patterns.…”
Section: Discussionmentioning
confidence: 99%
“…17 In another study of 1768 patients, 18 our patient cohorts were small, our total reintervention rate (7.4%) in the CxL group was lower than that reported in large single center series (12.5% to 19.2%). 18,21 Besides stent-graft design, aortoiliac axis geometry, and the distal landing zone, limb orientation could contribute equally to limb thrombosis. The geometry of the conduit is, in fact, one of the most important determinants of local flow patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the under‐lying determinants of aneurysm‐related complications following EVAR are predominantly morphological rather than physiological9–11. In contrast to earlier recommendations12, modern reporting standards for EVAR now stress the need for accurate reporting of aneurysm morphology using images processed on a workstation, permitting three‐dimensional (3D) reconstruction, to place clinical outcomes in context13–15.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these two deaths, the morbidity, mortality, hospital stay, and reintervention rates for this cohort compare well with similar figures from large EVAR series. 2,20,21 This unit estimates that once fully operational, the national AAA screening program for England will detect approximately 3000 aneurysms every year in men aged 65. These men will have a projected life expectancy of 21 years 22 at the time of their AAA diagnosis.…”
Section: Discussionmentioning
confidence: 99%